THE CREATION PROCESS OF THE PELUK JIWA DANCE WITH DEAF CHILDREN - Wardanny, Smirna; Widyastutieningrum, Sri Rochana (ISI Press Institut Seni Indonesia Surakarta, 2023)
Adopting a distinctive dance with movements and musical accompaniment to children with hearing impairments is exceptional. One can imagine the process and complexity that surrounds it. This article illustrates the PelukJiwa dance creation process by Jonet Sri Kuncoro and WasiBantolo with deaf children. This analysis employs a qualitative method by observing the creation and staging of the dance and conducting interviews with dancers, choreographers, and directors, which are then descriptively analyzed qualitatively. The analysis outcomes indicate that the process of creating this dance incorporates dance movement, theme selection, technique, exploration, organization, cohesion, and presentation. In addition, the performance conveys a message of social equality for deaf and normal children.